Interaction among experience, teaching performance and student’s learning at university level - Borgobello, Ana (2013)
This experimental study approaches characteristics of three university teachers' classes with different levels of experience. According to the literature, experienced teachers more often than not are adaptable to different contexts. However, novice teachers are usually focused on specific class contents to be evaluated. Three teachers were selected, a Professor, and two Assistants (a university level one and an undergraduate). We gave them a source text to teach 10 students each one. After that, students' knowledge was evaluated with a post-test and a self-evaluation. The characteristics of the three classes were evaluated by external judges and the students themselves. Moreover, theme and sequential submission analyses following the source text were made. Results show differences in each of the analyzed aspects according to the literature.